EFEKTIVITAS PERMAINAN STICO TERHADAP KEMAMPUAN KONSEP DASAR HITUNG, MEMBEDAKAN WARNA DAN MELATIH MOTORIK HALUS PADA SISWA PAUD - Dzulkifli Dzulkifli; andini dwi arumsari (MOTORIC, 2022)
STICO (Stick To Count Match And Color) is a learning media in the form of an educational game tool (APE) which aims to help early childhood in learning the basic concepts of counting, and knowing colors. This game is also designed to train fine motor skills in PAUD students. This study uses experimental research with a quantitative approach, the research design used is Pre-Experimental Design with One-Group Pretest-Posttest Design model. The data collection technique used in this study was observation with the checklist method. This research was conducted at the Kasih Bunda PAUD which is located in Ndono Hamlet, Temu Village, Kanor District, Bojonegoro. The subjects in this study were 5 PAUD Kasih Bunda students aged 4 years. The results of the study are that after the researchers carried out treatment for 6 times not in a row for 2 days in the morning, afternoon and evening at the same time on the first and second days using the STICO that the researchers made and the posttest results showed that the subjects experienced an increase in the basic skills of counting concepts, distinguishing colors and improving the subject's fine motor skills.Keywords: Educational game tools, basic arithmetic concept skills, ability to distinguish colors, fine motor skills